1972
DOI: 10.1126/science.177.4055.1209
|View full text |Cite
|
Sign up to set email alerts
|

Narcotic Drugs: Effects on the Serotonin Biosynthetic Systems of the Brain

Abstract: The effects of short- and long-term administration of morphine on the activity of two measurable forms of rat brain tryptophan hydroxylase were studied. Morphine administration produced an immediate decrease and a long-term increase in the nerve ending (particulate) enzyme activity but did not change the cell body (soluble) enzyme activity. Cocaine administration demonstrated a short-term decrease in measurable nerve ending enzyme activity that was due to the inhibition of the high affinity uptake (the Michael… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

1975
1975
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…It is possible that cocaine stimulates 5-HT receptors directly and thus indirectly modifies release in vivo through a negative feedback system or that it directly inhibits 5-HT release. The effect of cocaine on 5-HT synthesis may also be partially mediated through a trans-synaptic feedback system (Anden, Corrodi & Fuxe, 1971), although tryptophan uptake appears to play a major role as shown by the in vitro studies (Knapp & Mandell, 1972). Our data are not sufficient to predict which, if any, of these mechanisms are involved.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…It is possible that cocaine stimulates 5-HT receptors directly and thus indirectly modifies release in vivo through a negative feedback system or that it directly inhibits 5-HT release. The effect of cocaine on 5-HT synthesis may also be partially mediated through a trans-synaptic feedback system (Anden, Corrodi & Fuxe, 1971), although tryptophan uptake appears to play a major role as shown by the in vitro studies (Knapp & Mandell, 1972). Our data are not sufficient to predict which, if any, of these mechanisms are involved.…”
Section: Discussioncontrasting
confidence: 44%
“…Knapp & Mandell (1972) have shown that cocaine in vitro decreased 5-HT synthesis by inhibition of tryptophan uptake and not by direct inhibition of tryptophan hydroxylase. However, inhibition of synthesis, especially in the presence of the blockade of 5-HT uptake known to be an effect of cocaine (Ross & Renyi, 1969), would be expected to result in a precipitous fall in brain 5-HT levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphine inhibits tryptophan hydroxylase activity and also sup presses REM sleep. Again, both phenomena show a rebound increase following morphine withdrawal (37,59). As far as the amphetamines are concerned, one study, in guinea pigs, demonstrated a rebound increase in monoamine oxidase activity following methamphetamine withdrawal (75).…”
Section: Rem Sleep and Brain Repairmentioning
confidence: 99%
“…At the same time, there also occurs a re bound increase in the duration of REM sleep (59). The rise in tryptophan hydroxylase activity following morphine withdrawal may be cited as another example (37). Morphine inhibits tryptophan hydroxylase activity and also sup presses REM sleep.…”
Section: Rem Sleep and Brain Repairmentioning
confidence: 99%